A POLITICAL APPROACH TO SEZAI KARAKOC’S “LITERARY WRITINGS” - DEMİREL, İdiris (SSD Journal, 2021)
Sezai Karakoç (1933 - ) is one of the most important living figures of Turkish thought and literature. In the context of literature, he is primarily at the forefront of his poetry. But in addition to poetry, he also put out various studies in different fields of literature and thought, such as stories, plays, essays, reviews, translations. It can be seen that Sezai Karakoç almost all of his works contain literature and art topics in a broader sense, for various occasions. In other words, his view especially poetry, literature and art, are spread over a wide range of books. However, although this is the case, there is also a three-book “Literary Writings” series that collects Karakoç’s approaches to art and literature. The author analyzes Turkish and world literature in his “Literature Writings.” It is seen that various political issues, especially civilization, Turkish-Islamic civilization, political currents, ideologies, social-political transformations, religions, historical-sociological issues, political regimes, are covered in these analyses. In 1960, the thinker started publishing a thought and art journal called ‘Resurrection.’ The Resurrection continued to exist in various forms until the early 1990s, sometimes with short and sometimes with long cycles and chapters. It should be said that the journal is a long-term, fertile and nutritious school for the Turkish world of art, literature and thought. It should also be noted that the Resurrection as a concept is a kind of sign and determinant for Karakoç to express his own thoughts, especially his own understanding of Islamic civilitazion. In addition to its direct political determinations, Karakoç also makes political determinations in indirect ways in evaluating notable literary and thought names such as Mehmet Akif, Yahya Kemal and Necip Fazıl Kısakürek. Both his “Literary Writings” and his other studies are among the concrete indicators of why he is not only a well-known man of letters, but also one of the most respected thinkers of Turkey. The purpose of this reviews is to examine Sezai Karakoç’s “Literary Writings” from a political point of view. A qualitative approach, not a quantitative one, was adopted as a method in the study. Documentary research has been conducted. It was thought that the data that will be revealed may be the findings that will accelerate the interdisciplinary studies in various fields of knowledge from literature to political science.